Clinical Implementation of a Scrubless Chlorhexidine/Ethatol Pre-Operative Surgical Hand Rub - Marchand, Richard; Theoret, Sylvie; Dion, Danielle; Pellerin, Michel (Operating Room Nurses Association of Canada Journal, 2008)
The objective of surgical scrubbing is to freduce the bioburden on the hands of the surgical team in hope that if gloves are punctured or torn, the number of bacteria released at the operation site will be minimal and therefore reduce the risk of site infection.